B Chromosomes in Genus Sorghum (Poaceae) - Bednářová, Martina; Karafiátová, Miroslava; Hřibová, Eva; Bartoš, Jan (Plants (Basel, Switzerland), 2021)
B chromosomes (Bs) are supernumerary dispensable genomic elements that have been reported in several thousand eukaryotic species. Since their discovery, Bs have been subjected to countless studies aiming at the clarification of their origin, composition, and influence on the carriers. Despite these efforts, we still have very limited knowledge of the processes that led to the emergence of Bs, the mechanisms of their transmission, and the effects of Bs on the hosts. In the last decade, sophisticated molecular methods, including next-generation sequencing, have provided powerful tool to help answer some of these questions, but not many species have received much attention yet. In this review, we summarize the currently available information about Bs in the genus Sorghum, which has so far been on the periphery of scientific interest. We present an overview of the occurrence and characteristics of Bs in various Sorghum species, discuss the possible mechanisms involved in their maintenance and elimination, and outline hypotheses of the origin of Bs in this genus.
Keywords: B chromosomes; phylogenesis; chromosome elimination; evolution; supernumerary chromosomes; Sorghum